Modulation of C-reactive protein and plasma omega-6 fatty acid levels by phospholipase A2 gene polymorphisms following a 6-week supplementation with fish oil. (December 2015) - Tremblay, B.L.; Rudkowska, I.; Couture, P.; Lemieux, S.; Julien, P.; Vohl, M.C.
Abstract: This clinical trial investigated the impact of a six-week supplementation with fish oil and single nucleotide polymorphisms (SNPs) in PLA 2 G 4 A and PLA 2 G 6 genes on total omega-6 fatty acid (n-6 FA) levels in plasma phospholipids (PL) and plasma C-reactive protein (CRP) levels in 191 subjects. Interaction effects between SNPs and supplementation modulated total n-6 FAs and CRP levels in both men and women. Associations between SNPs and total n-6 FA levels and between SNPs and CRP levels were identified in men, independently of supplementation. Supplementation decreased total n-6 FAs without affecting plasma CRP levels. Changes in CRP levels correlated positively with changes in total n-6 FAs in men ( r =0.25 p =0.01), but not in women. In conclusion, total n-6 FA levels in plasma PL and plasma CRP levels are modulated by SNPs within PLA 2 G 4 A and PLA 2 G 6 genes alone or in combination with fish oil supplementation.